INDONESIAN banking in commemoration of 50 th anniversary PERBANAS (National Private Banks Association) Jerry Marmen Simanjuntak ... [et al.] - Simanjutak, Jerry Marmen (Centre for finance & Banking information PERBANAS Business school)
vii, 307 hlm ilus 29 cm